Mathematic Learning Material Capabilities on Special Needs - Wuryanti, Sri; Fahmi, Fahmi; Hamiseno, Giri Sarana (Indonesian Journal of Disability Studies, 2021)
Abstract: The purpose of this study was to see the application of students with special needs in inclusive schools and their absorption of Mathematics subject matter in the SMA National Examination 2018/2019 academic year. Although, the National Examination has legally abolished, the results of the last National Examination 2018/2019 can still be used to capture students' minimum academic abilities and also for reflection in order to improve the quality of education better. The ability of students can be seen from the results of the national exam, while the absorption of mathematics can be seen from the proportion of students with special needs in inclusive schools who can correctly answer questions on the National Mathematics Exam. The population of this study were all high school level students who took the National Examination for the 2018/2019 academic year, while the research sample was all inclusive high school students who took the National Examination for the 2018/2019 academic year. The data used is secondary data, namely the SMA National Exam data for the 2018/2019 academic year. Data analysis used Excel software, and then descriptive statistical analysis was carried out. The results showed the highest score of the National Mathematics Examination for students with special needs in inclusive schools was 54.02 and the lowest was 22.69 with an average score of 39.43. The average score of Mathematics for the Science Department is 45.66 (included in the poor category), the Language Department is 40.04 (including the poor category), while the Social Science Department is 29.28 (including the low category). The highest average absorption power of Mathematics in the Science department is 30%, in the scope of Algebra material, the lowest absorption is 23% in the scope of calculus material. In the social studies department, the highest average absorption power in mathematics is 29% each for algebra and statistics, the lowest absorption rate is 18% in the scope of Geometry and Trigonometry. Meanwhile, in the Language Department, the highest average absorption is algebra 38%, the lowest is 30% in the scope of Geometry and Trigonometry. The range of values for participants with special needs is very large so it needs assistance to improve the abilities of students. The weakness of special needs students in Mathematics is the material scope of Geometry and Trigonometry.